Kişilik Hakkı İhlallerinde Yetkili Mahkemeler - (:unkn) unknown (My University, 2017)
Kişilik hakkı ihlallerinin sayısındaki artış ve bu ihlallerin gerçekleştirilmesi ile etki ve sonuçlarının farklı ülkelerde meydana gelmesi bu konularda başvurulacak yetkili mahkemelerin tespitinin önemini artırmaktadır. Kişilik hakkı ihlalleri durumunda başvurulacak yetkili mahkemeler konusunda hukukumuzda esas alınması gereken düzenlemeler, Türk Medeni Kanunu (TMK) m. 25/son ile Hukuk Muhakemeleri Kanunu (HMK) m. 16'dır. Bu düzenlemeler, aynı zamanda Milletlerarası Özel Hukuk ve Usul Hukuku Hakkında Kanun (MÖHUK) uyarınca Türk Mahkemelerinin milletlerarası yetkisini belirlediğinden özellikle üzerinde durulması gereken düzenlemelerdir

The importance of determination of place of jurisdiction in the case of violation of personal rights is getting more important issue because of the increasing number of the violation of personal rights and state difference between the venue of the violation and the place that its effects and results has been occured. In Turkish Law, Turkish Civil Code (TMK) Art. 25/5 and Turkish Civil Procedure Code (HMK) Art. 16 are the articles that determine the place of jurisdiction in the case of violation of personal rights. These articles determines also international place of jurisdiction according to Code of International Private and Civil Procedural Law (MÖHUK)
Place of Jurisdiction in Case of Violation of Personal Rights
Keywords: Hukuk